(3TQM TQGFY GdESdGes - (3cGTa GdZWGA, gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdRcGI, hgj dZI JYfj Gdfeh hGdWgGQI, hbO GSJYedJ aj GdcJGH hGdSfI HGdeYfjjf, haj YQa CYd GdTQY GSe ebOGQ eYdhe jLH ENQGLg ef GdeGd HTQhWs
(3BNQgG (B:s
(3BNQgG(B: (3dG jLH ENQGL GdYjf MJi aj GdCfYGe Ydi GdUM Hd jLhR HOdG OaY GdbjeI GdShbjI hEf cGfJ YQhkVG hHjY GdLfS Ke GMJSGH bjeJg CMhW hENQGL GdYjf CaVds
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis